SCIENTIFIC ARTICLES WRITING TRAINING TO IMPROVE STUDENTS' PROFESSIONALISM IN PREPARING SCIENTIFIC ARTICLES AND PUBLICATIONS IN THE SINTA ACCREDITED NATIONAL JOURNAL - Sam Hermansyah (La Ogi : English Language Journal, 2024)
The point of this movement is to supply instruction to understudies almost logical articles and strategies for compiling logical articles, national diaries and licensed national diaries, give tips and traps in getting into distributions in SINTA authorize national diaries, move forward students' capacities incompose and distribute logical papers in licensed national diaries. The strategy utilized is the address strategy, where the fabric displayed is an clarification of logical work, methods for composing logical papers, logical diaries and distributions in SINTA certify national diaries, dialogs, where members are given the opportunity to examine the fabric displayed, the assignment of compiling logical papers by giving extraordinary help, checking and assessment of these exercises which are carried out intermittently. The comes about gotten from this action are expanded understudy information in terms of logical articles, the systematics of composing logical articles, and logical distribution strategies in SINTA-accredited national diaries as prove by the comes about of posttest scores, expanding the quality of logical articles created by understudies, which after holding this benefit program understudies are able to type in logical articles with direction from the group, expanding the amount of logical articles created by understudies, where there are as of now 20 understudy articles that have been submitted to the benefit group for audit and then given suggestions for distribution in one of the logical articles. The most conclusion from this benefit movement is that this action can give incredible benefits for understudies, to be specific by giving instruction almost logical articles and strategies for compiling logical articles, distribution methods in SINTA-accredited national diaries and spurring them to type in logical articles and distributions in SINTA-accredited national diaries